Odpowiedź :
Odpowiedź:
[tex](x^{2} -5x-20)^{2} = (x^{2} -2x-10)^{2} \\(x^{2} -5x-20) * (x^{2} -5x-20) = (x^{2} -2x-10) * (x^{2} -2x-10)\\x^{4}+25x^{2} + 400 -10x^{3} -40x^{2} +200x = x^{4} +4x^{2} +100 -4x^{3}-20x^{2} +40x}\\x^{4} -10x^{3} -15x^{2} +200x+400 = x^{4} -4x^{3} -16x^{2} +40x+100\\-6x^{3}+x^{2} +160x+300=0[/tex]
[tex]-6x^{3} -15x^{2} +16x^{2} +40x+120z+300=0\\-3x^{2} *(2x+5)+8x*(2x+5)+60(2x+5)=0\\-(2x+5)*(3x^{2} -8x-60)=0\\-(2x+5)*(3x^{2} +10x-18x-60)=0\\-(2x+5)*(x*(3x+10)-6(3x+10))=0\\-(2x+5)*(3x+10)*(x-6)=0\\x=-\frac{5}{2} \ x=-\frac{10}{3} \ x=6[/tex]
Szczegółowe wyjaśnienie: